2008
DOI: 10.1007/s11999-007-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Changes of Bone Metabolism in Normal and Delayed Union of the Spine

Abstract: Time-dependent changes in bone markers in delayed or nonunion of vertebral fracture were compared with those of normal union. Thirty-three patients with a fresh vertebral fracture were enrolled. Urinary Type I collagen C-terminal telopeptide, pyridinoline, deoxypyridinoline, serum C-terminal telopeptide, and N-midportion of osteocalcin (OC N-mid ) were determined at the time of hospital admission (within 24 hours after the fracture event in all cases) and at 2, 4, 12, 24, and 48 weeks thereafter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…For the fracture healing process, the changes occurring during bone degradation (resorption) and production (formation) are more intense compared to those seen in the remodeling period in all bone fractures. [ 7 15 ] Many neurosurgeons advocate using the fusion surgery from the posterior in unstable vertebral fractures to complete the healing process with no deformation and to ensure stability. All transpedicular implants are used to provide vertebral reduction until the fracture heals and fusion occurs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the fracture healing process, the changes occurring during bone degradation (resorption) and production (formation) are more intense compared to those seen in the remodeling period in all bone fractures. [ 7 15 ] Many neurosurgeons advocate using the fusion surgery from the posterior in unstable vertebral fractures to complete the healing process with no deformation and to ensure stability. All transpedicular implants are used to provide vertebral reduction until the fracture heals and fusion occurs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 28 29 ] These nonsurgical patients were included in the control group and they had been mobilized with a corset after a resting period varying from 1 to 3 weeks. Patients were asked to use the corset for 3 months[ 15 19 ] because previous studies have showed increased serum and urinary levels of bone production and degradation products in patients with osteoporosis;[ 7 ] osteoporotic patients were not included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations